2014
DOI: 10.1002/eji.201344238
|View full text |Cite
|
Sign up to set email alerts
|

IL‐15 regulates Bcl‐2 family members Bim and Mcl‐1 through JAK/STAT and PI3K/AKT pathways in T cells

Abstract: Maintenance of T cells is determined by their survival capacity, which is regulated by IntroductionDuring maturation and in the mature state, T-cell homeostasis is regulated by two processes: apoptosis and proliferation [1,2]. In resting T cells, apoptosis is largely determined by the Bcl-2 family of proteins, and T-cell survival is regulated by the effect that extrinsic signals have on Bcl-2-family proteins [3]. The main stimuli in the regulation of both proliferation and survival are signals received by comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
1
44
0
2
Order By: Relevance
“…Instead, we found that gdT-IFNg cells upregulate Mcl-1 after IL-7 and IL-15 stimulation, but particularly the latter. Although IL-15 can also increase Mcl-1 in ab T cells, it is never as marked as the effect of IL-7 (36,37). This increase in Mcl-1 by IL-15 is instead reminiscent of the response of NK cells to IL-15 (38), suggesting that gd T cells blend aspects of innate and adaptive cell behavior, not only for their activation, but also for their survival.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, we found that gdT-IFNg cells upregulate Mcl-1 after IL-7 and IL-15 stimulation, but particularly the latter. Although IL-15 can also increase Mcl-1 in ab T cells, it is never as marked as the effect of IL-7 (36,37). This increase in Mcl-1 by IL-15 is instead reminiscent of the response of NK cells to IL-15 (38), suggesting that gd T cells blend aspects of innate and adaptive cell behavior, not only for their activation, but also for their survival.…”
Section: Discussionmentioning
confidence: 98%
“…This short half-life is physiologically significant, as a stabilized form of Mcl-1 ameliorated the polycystic kidney disease and lymphopenia arising in mice lacking pro-survival Bcl-2 (257). Common gamma chain cytokines induce Mcl-1 in resting T cells in vitro , independent of mRNA levels and protein stability, suggesting translational regulation (258). Mcl-1 protein stability is controlled by T cell receptor (TCR) affinity-dependent interleukin-2 signaling (259).…”
Section: Bcl-2 Family Membersmentioning
confidence: 99%
“…by guest www.bloodjournal.org From the PI3K-Akt-mTOR signaling and attenuate intrinsic apoptosis pathway. [31][32][33] Alternatively, mTOR inhibition may not only eliminate abnormally differentiated cells and reduce their proliferation but also to some extent revert their abnormal programming. In contrast, DNT cells from MMF-treated patients with ALPS retained the abnormal differentiation and mitotic activity, indicating that pharmacological regulation of the mTOR pathway might offer a superior therapeutic option than MMF therapy.…”
Section: P-aktmentioning
confidence: 99%